Faktor-Faktor Yang Mempengaruhi Kualitas Pelayanan Publik Pada Kantor Kelurahan Bahu Kecamatan Malalayang Kota Manado - Bawole, Deyvy Setiawan; Lengkong, Florence Daicy; Kiyai, Burhanudin (Sam Ratulangi University, 2015)
The quality of public services is the actual issues that are important in the era of bureaucraticreform in Indonesia today, including in the area of Bahu village district. Malalayang Manado. Theformulation of the problem, namely the factors that influence the quality of public services at the VillageOffice Shoulder. The aim of this study was to determine the factors associated with the quality of publicservice employees in the Village Shoulder.Public service is a process of assistance to others in ways that require particular sensitivity andinterpersonal relationships to create satisfaction and success. Factors to be examined Public Service iscovering the Organizational Structure (X1), Ability Apparatus (X2) and System Services (X3). While thePublic Satisfaction (Y) is feeling happy or upset someone as a result of a comparison between the perceivedperformance with that expected.The method used is qualitative method. Data collected through surveys, interviews and questionnaires(questionnaire) in 95 households as respondents. Data were analyzed using Multiple Linear RegressionAnalysis, Correlation Coefficient and Coefficient of Determination, and Hypothesis Testing simultaneouslywith F test and partially by t test at significance level Î± = 0.1.Based on the results of hypothesis testing with Multiple Linear Regression Analysis equation Y =11.232 + 0.298 X1 + 0.138 X2 + 0.122 X3. The value of coefficient of determination (R2) = 46.7% and thecorrelation coefficient (R) = 21.9%, which indicates that factors such as the organizational structure ofpublic services, the ability of the apparatus and system service has a relationship as well as the proportion ofcontribution or donation to the satisfaction of the people , While Hypothesis simultaneously produces a valueof F = 8.482 greater than F table = 3.10. While partially produce tcount each variable: 4.268; 1.860 and1.712 greater than the value of table = 1.66; so the hypothesis can be accepted.Then, based on the calculation above it can be concluded that factors such as the Public ServiceQuality Organizational Structure, Apparatus and System Services Capabilities can affect CommunitySatisfaction. So it is suggested to the leadership of the Village Office Shoulder and relevant Governmentagencies to pay attention to and improve these factors in order to increase public satisfaction Shouldervillage.Keywords: quality of public services, organizational structure, the ability of the apparatus, system service,community satisfaction